Values across the border: axiological content of changing identities in the Russian-Ukrainian borderlands = Wartości ponad granicą: czy istnieje podział kulturowy i cywilizacyjny na pograniczu rosyjsko-ukraińskim? - Sapryka, Viktor; Zvyeryeva, Olga (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The present-day conflict between Russia and Ukraine has lead to drastic changes both in official foreign policies and in the population?s attitude bringing the two nations to the point of a cultural and civilizational split. At the same time, the bordering regions were always known for their hybrid identities manifested, among other means, via specific axiological and behavioral patterns. In our paper we will study the changes of values across the Russia-Ukraine border to answer the question whether the borderlands witness the same cultural and civilizational split as the countries or whether we can talk about more stable and resilient border identities.
Keywords: identity; borderland; Russian-Ukrainian relations; tożsamość; pogranicze; relacje rosyjsko-ukraińskie